2021
DOI: 10.3389/fbioe.2021.645019
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the Femoral Offset for Restoring Physiological Hip Muscle Function in Patients With Total Hip Arthroplasty

Abstract: ObjectiveFemoral offset (FO) restoration is significantly correlated with functional recovery following total hip arthroplasty (THA). Accurately assessing the effects of FO changes on hip muscles following THA would help improve function and optimize functional outcomes. The present study aimed to (1) identify the impact of FO side difference on the hip muscle moment arms following unilateral THA during gait and (2) propose the optimal FO for a physiological hip muscle function.MethodsIn vivo hip kinematics fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…It has been reported that reduced femoral offset negatively affected range of motion due to impingement and reduced abductor lever ( 32 ). Gait analysis has shown that changes in femoral offset also influence the function of external rotator, extensor and short flexor muscle during different phase of gait ( 33 ). On the other hand, one study found that significantly increased femoral offset was an important source of elevated ions in metal on polyethylene THA, suggesting possible increased contact force and accelerated wear ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that reduced femoral offset negatively affected range of motion due to impingement and reduced abductor lever ( 32 ). Gait analysis has shown that changes in femoral offset also influence the function of external rotator, extensor and short flexor muscle during different phase of gait ( 33 ). On the other hand, one study found that significantly increased femoral offset was an important source of elevated ions in metal on polyethylene THA, suggesting possible increased contact force and accelerated wear ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, Hu et al quantified the effect of femoral offset difference post-THA [26]. They reported that an appropriate increase of 2-3mm in femoral offset could improve the recovery of hip abduction and external rotation function [26].…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, Hu et al quantified the effect of femoral offset difference post-THA [26]. They reported that an appropriate increase of 2-3mm in femoral offset could improve the recovery of hip abduction and external rotation function [26]. Consequently, an optimal femoral offset calculated pre-operatively via digital templating, rather than blindly increasing this distance, could reduce muscle imbalance, gait instability, and THA dislocations [26].…”
Section: Discussionmentioning
confidence: 99%
“…Based on a 3D computer model, Delp et al (1996) found that superolateral placement of the HCOR resulted in an average reduction 28% in the abductor muscle moment arm. This could lead to muscle imbalance and prosthetic joint dislocations ( Renkawitz et al, 2016 ; Hu et al, 2021 ). Further, Bicanic et al (2009) quantified the relationship between the displacement of HCOR and the joint response force in the experiment and found that upshifting the HCOR by 1 mm will increase the joint response force by 0.1%.…”
Section: Discussionmentioning
confidence: 99%